Stimulus predictability moderates the withdrawal strategy in response to repetitive noxious stimulation in humans - Jure, Fabricio A. (2020)
Nociceptive withdrawal reflex (NWR) is a protective reaction to a noxious stimulus, resulting in withdrawal of the affected area and thus preventing potential tissue damage. This involuntary reaction consists of neural circuits, biomechanical strategies, and muscle activity that ensure an optimal withdrawal. Studies of lower limb NWR indicate that the amplitude of the NWR is highly modulated by extrinsic and intrinsic factors, such as stimulation site, intensity, frequency, and supraspinal activity, among others. Whether the predictability of the stimulus has an effect on the biomechanical strategies is still unclear. This study aimed to evaluate how the predictability of impending noxious stimuli modulate the NWR reaction in the lower limb. NWR was evoked on fifteen healthy participants by trains of electrical stimuli on the sole of the foot and was measured in one distal (tibialis anterior) and one proximal (biceps femoris) muscle. The predictability was manipulated by giving participants prior information about the onset of the stimulus trains and the number of delivered stimuli per train. Results showed that the predictability of the incoming stimuli differentially modulates the muscle activity involved in the NWR reaction. For the most unpredictable stimulus train, larger NWR at distal muscles were evoked. Furthermore, the stereotyped temporal summation profile to repeated stimulation was observed when the stimulus train was completely predictable, while it was disrupted in proximal muscles in unpredictable conditions. It is inferred that the reflex response is shaped by descending control, which dynamically tunes the activity of the muscles involved in the resulting reaction. NEW & NOTEWORTHY Innate defensive behaviors such as reflexes are found across all species, constituting preprogrammed responses to external threats that are not anticipated. Previous studies indicated that the excitability of the reflex arcs like spinal nociceptive withdrawal reflex (NWR) pathways in humans are modulated by several cognitive factors. This study assesses how the predictability of a threat affects the biomechanical pattern of the withdrawal response, showing that distal and proximal muscles are differentially modulated by descending control.